1993
DOI: 10.1002/ijc.2910550407
|View full text |Cite
|
Sign up to set email alerts
|

Lack of allelic deletion and point mutation as mechanisms of p53 activation in human malignant melanoma

Abstract: To investigate the role of the p53 tumor-suppressor gene in the development of human melanoma, loss of heterozygosity (LOH) of p53 was studied in 46 cases of melanoma by a polymerase-chain-reaction/restriction-fragment-length polymorphism (PCR/RFLP) analysis, and p53 mutations were assessed in 51 cases of melanoma by a polymerase-chain-reaction/single-strand-conformation polymorphism (PCR/SSCP) analysis. Frozen tumors and paraffin samples were used in the study. We were not able to detect any allelic loss in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
2
7

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 15 publications
1
54
2
7
Order By: Relevance
“…These findings sharply contrast with the situation in human melanoma, in which p53 mutations are not commonly detected (Volkenandt et al, 1991;Castresana et al, 1993;Weiss et al, 1993;Lübbe et al, 1994;Albino et al, 1994;Florenes et al, 1994;Montano et al, 1994;Sparrow et al, 1995;Hartmann et al, 1996;Papp et al, 1996), with frequencies ranging from 0 to 6% in tumour samples (Castresana et al, 1993;Florenes et al, 1994;Lübbe et al, 1994;Papp et al, 1996). However, mutations in the N-ras gene have been shown to occur in at least 15% of melanomas (van Elsas et al, 1996) and occur more frequently in tumours from sun-exposed body sites compared with tumours from intermittently or unexposed sites, implicating sun exposure in the aetiology of these melanomas (van Elsas et al, 1996).…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…These findings sharply contrast with the situation in human melanoma, in which p53 mutations are not commonly detected (Volkenandt et al, 1991;Castresana et al, 1993;Weiss et al, 1993;Lübbe et al, 1994;Albino et al, 1994;Florenes et al, 1994;Montano et al, 1994;Sparrow et al, 1995;Hartmann et al, 1996;Papp et al, 1996), with frequencies ranging from 0 to 6% in tumour samples (Castresana et al, 1993;Florenes et al, 1994;Lübbe et al, 1994;Papp et al, 1996). However, mutations in the N-ras gene have been shown to occur in at least 15% of melanomas (van Elsas et al, 1996) and occur more frequently in tumours from sun-exposed body sites compared with tumours from intermittently or unexposed sites, implicating sun exposure in the aetiology of these melanomas (van Elsas et al, 1996).…”
contrasting
confidence: 78%
“…21% vs 0-6% in tumours (Castresana et al, 1993;Florenes et al, 1994;Lübbe et al, 1994;Papp et al, 1996) and 27% vs 11-25% in cell lines (Volkenandt et al, 1991;Weiss et al, 1993;Albino et al, 1994;Papp et al, 1996). One report describes p53 mutations in exons 7 and 8 in 15% of the tumours studied (Akslen et al, 1998).…”
Section: P53 Mutation Frequencies In Skin Cancermentioning
confidence: 99%
“…However, some melanomas which were immunopositive for p21 WAF1 contained foci within the tumour which were strongly immunopositive for p53 but which were p21 WAF1 negative. Because p21 WAF1 is mutated infrequently in melanoma (Vidal et al, 1995), it is likely that p53 was mutated in these clones, and suggests that when the TP53 gene becomes mutated (albeit at a low frequency) in cutaneous melanoma it occurs as a late event during melanoma progression (Castresana et al, 1993;Albino et al, 1994;Florenes et al, 1994;Lubbe et al, 1994;Montano et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This abnormal expression of wild-type p53 protein was also found in normal cells of a patient from a family with a history of cancer (Barnes et al, 1992) and, more recently, a new case of Li-Fraumeni was reported in which no mutation in the coding sequence of the p53 gene was detected (Birch et al, 1994). In all cases, stabilization of the p53 protein depends on factors other than p53 gene mutation, such as (1) binding to other molecules of cellular (mdm2 gene product) or viral origin blocking p53 in an inactive conformation; and/or (2) (Lang et al, 1994), melanomas (Castresana et al, 1993) and testis cancer (Peng et al, 1993), and that nuclear exclusion of p53 might also be one way of inactivating p53 in breast cancer (Moll et al, 1992). Nuclear exclusion of wild-type p53 is suggested in a study showing its cytoplasmic accumulation in colorectal cancers (Bosari et al, 1995) with a higher prevalence in advanced tumours (Sun et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…However, the literature concerning the prognostic value ofp53 immunoreactivity is controversial, as the results of IHC assays cannot be accepted as evidence of p53 gene mutation (Battifora et al, 1994). In addition, there is no clear picture concerning the significance of wild-type overexpression observed in several studies on colorectal adenomas (Pignatelli et al, 1992;Pignatelli et al, 1992;Tominaga et al, 1993) and demonstrated in anaplastic astrocytomas (Lang et al, 1994), breast cancer (Moll et al, 1992), melanomas (Castresana et al, 1993), testis cancer (Peng et al, 1993) and hepatic tumours of childhood (Kennedy et al, 1994 Primer 11 Sense Intron 6 5'-GTC TCC CCA AGG CGC ACT GG-3' Primer 12…”
Section: Materials and Methods Materialsmentioning
confidence: 99%